1990
DOI: 10.1111/j.1439-0310.1990.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggression among Lekking Male Fallow Deer (Dama dama): Territory Effects and Relationship with Copulatory Success

Abstract: We studied the aggressive behavior of territorial male fallow deer (Dama dama) at two leks. Daily number of escalated fights was not correlated with number of matings. A dominance index including all agonistic interactions was weakly correlated with copulatory success; the correlation was stronger when each half of the rut was considered separately. Dominance likely changed over the rut due to fatigue. We ranked lek territories by the number of copulations seen in each. Males that won fights were likely to tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…During the rut, the frequency of fights was closely related to the number of mating opportunities, indicating an increased tendency for males to risk potentially serious conflict in the presence of a valuable transient resource (Enquist & Leimar 1987). This is in contrast to the findings of Festa-Bianchet et al (1990), who found that the daily numbers of fights and matings across fallow deer leks were either weakly correlated, or not correlated at all. However, in the same population, the number of matings and fights on individual lek territories were correlated .…”
Section: Matings Interaction Hates and Fight Ratesmentioning
confidence: 62%
See 1 more Smart Citation
“…During the rut, the frequency of fights was closely related to the number of mating opportunities, indicating an increased tendency for males to risk potentially serious conflict in the presence of a valuable transient resource (Enquist & Leimar 1987). This is in contrast to the findings of Festa-Bianchet et al (1990), who found that the daily numbers of fights and matings across fallow deer leks were either weakly correlated, or not correlated at all. However, in the same population, the number of matings and fights on individual lek territories were correlated .…”
Section: Matings Interaction Hates and Fight Ratesmentioning
confidence: 62%
“…In addition, the ma-jority of fights between territorial males on the fallow deer leks in question had no clear winners. Thus, they could not contribute to estimates of dominance rank (Clutton-Brock et al 1988;Festa-Bianchet et al 1990). The dominance and fighting ranks in the present study were calculated using the results of agonistic interactions between males that ranged widely.…”
Section: Mating Success Social Maturity and Dominance Rankmentioning
confidence: 99%
“…In polygynous species, male reproductive success depends on their ability to outcompete rival males and on the number of females they can fertilize (Festa-Bianchet et al 1990, Komers et al 1994, Clutton-Brock and McAucliffe 2009, Clutton-Brock 2017. Thus, males usually compete intensely for mates, which may create large variation in male mating success (Emlen andOring 1977, Clutton-Brock 1988) and, in turn, strong selection on sexual traits (such as horns, antlers, tusks; Geist 1966, Andersson 1994.…”
Section: Introductionmentioning
confidence: 99%
“…A major line of work in ecological and evolutionary research aims at investigating relationships between individual mating success and sexually dimorphic traits, such as male weaponry, ornaments (e.g., Clutton-Brock 1988;Lappin & Husak 2005) or behaviours (Festa-Bianchet et al 1990;Fiske, Rintamaki & Karvonen 1998;Kelly 2008;Schuett, Godin & Dall 2011). The overarching goal is to understand the agents of sexual selection (Kirkpatrick & Ryan 1991;Andersson 1994;Jennions et al 2012) and to predict their evolutionary consequences, eventually explaining how individual variation in sexually selected traits is maintained.…”
Section: Introductionmentioning
confidence: 99%